2018
DOI: 10.1186/s12903-018-0522-6
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and radiographic evaluation of biodentine versus calcium hydroxide in primary teeth pulpotomies: a retrospective study

Abstract: BackgroundPulpotomy is the surgical removal of the entire coronal pulp with preservation of the radicular pulp vitality. The purpose of this retrospective study was to evaluate the clinical and radiographic success of pulpotomy of primary molars using two materials, biodentine and calcium hydroxide.MethodsRecords of 400 primary molars in 360 paediatric participants (mean age: 7.5 ± 1.6 years, ranging from 5 to 9 years) with dental caries who required pulp therapy were included in this study. Biodentine was use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
6

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 21 publications
1
21
0
6
Order By: Relevance
“…The advantage of biomaterials containing mineral trioxide and calcium silicate consists in their potential bioactive properties [1][2][3]5,7,8,31]. Bioactivity can be defined as materials that elicit a specific biological response at the interface between tissues and the material, which results in the formation of a bond [32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The advantage of biomaterials containing mineral trioxide and calcium silicate consists in their potential bioactive properties [1][2][3]5,7,8,31]. Bioactivity can be defined as materials that elicit a specific biological response at the interface between tissues and the material, which results in the formation of a bond [32].…”
Section: Discussionmentioning
confidence: 99%
“…This differentiation was accompanied by expression of odontoblast-associated genes. Also, other in vitro studies, enumerate the positive aspects of Biodentine TM , such as low cytotoxicity [37], good biocompatibility, bioactivity [1][2][3]5,7,8,31,38] and biomineralization [7,8,39]. Some in vitro studies have shown better sealing ability [40], higher mechanical compressive strength and microhardness [38,41] when compared to other bioceramic materials, suggesting that it may be used as an effective temporary sealant [42].…”
Section: Discussionmentioning
confidence: 99%
“…Ainda, concluiu que o cimento resinoso ACTIVA manifestou uma resposta inflamatória inferior aos cimentos de silicato de cálcio e apresentou o maior grau de biocompatibilidade para os tecidos subcutâneos, por meio da diminuição da intensidade da inflamação, seguida de uma remodelação dos tecidos e um padrão de cicatrização superior. Além disso, Caruso (2018) retrata que o Biodentine é um cimento à base de silicato de cálcio, que possui propriedades bioativas, não causa indícios de reposta moderada ou grave inflamação pulpar, além da capacidade de estimular a renovação do tecido duro.…”
Section: Resultsunclassified
“…Posteriormente, mediante o reconhecimento, seleção e ordenação das informações dos documentos, realizou-se o processo de leitura do material viabilizando o entendimento e a compreensão em relação ao que o autor afirma com o problema para o qual se almeja resposta. Em relação as principais aplicabilidades clínicas do cimento biocerâmico endodôntico, a maior parte dos materiais selecionados nas bases de dados demonstrou que os materiais estudados exibiam diversas possibilidades de aplicações clínicas, dentre elas, destacam-se a apexificação/apicificação, capeamentos pulpares, diversos procedimentos endodônticos, formação de barreiras apicais, obturações retrógradas, preenchimento do canal radicular, pulpotomias, reabsorção radicular inflamatória (interna e externa) e reparação de perfurações nas raízes (Al-Haddad, Aziz & Che, 2016; Bueno, 2016;BenettI, 2018;Caruso, 2018). Além disso, esses materiais apresentam propriedades físico-químicas e biológicas satisfatórias, de acordo com os padrões estabelecidos.…”
Section: Metodologiaunclassified
“…O tamanho mínimo da amostra foi calculado com base em dados de um estudo prévio (Caruso et al, 2018). O erro alfa e beta foram considerados de 5% e 20%, respectivamente.…”
Section: Cálculo Amostralunclassified